Propriedades antitumorais do açaí (Euterpe oleracea, Mart., 1824) e avaliação do desbalanço oxidativo relacionado ao genótipo da SOD2 em células saudáveis - Jobim, Micheli Lamberti (2019)
Cancer is one of the main problems of public health worldwide, and in most cases occurs in cells of epithelial origin, since they have a high proliferative rate and have limited characteristics of cell senescence. These cells constantly suffer from intrinsic and extrinsic aggression, generating oxidative stress and consequently the loss of their physical integrity, which is fundamental for tissue homeostasis and the prevention of deleterious diseases such as cancer. An antioxidant-rich diet could minimize the effects of oxidative stress by helping to treat and prevent different types of cancer. The fruit Euterpe oleracea (açaí) widely consumed in Brazil, has bioactive substances (orientin, p-coumaric acid, apigenin) that have antitumor, antioxidant properties, among others. Therefore, the aim of the present study was to evaluate the in vitro antitumor effect of Euterpe oleracea (açaí) hydroalcoholic extract on prostate cancer cells (DU 145) and colorectal cancer cells (HT-29), besides the genoprotective effect on keratinocyte cells (HaCat) subjected to pharmacological imbalance superoxide-hydrogen peroxide (S-HP). Firstly, we used healthy keratinocyte cells exposed to paraquat and porphyrin, causing an S-HP imbalance to verify the possible causal mechanism, evaluating cell viability and proliferation parameters, markers of oxidative stress and DNA damage. After we used the acai hydroalcoholic extract in different concentrations against the prostate cancer lineage (DU145) where we analyzed the parameters of cell viability and proliferation, changes in the cell cycle and activation of the apoptotic pathway and genes associated with apoptosis and cell cycle. Already the colorectal cancer lineage (HT-29) was exposed to different concentrations of açai extract, as well as its main biotive molecules (orientin, apigenin and p-coumaric acid). The parameters of cell viability and proliferation, alterations in the cell cycle, activation of the apoptotic pathway, through spectrophotometric and fluorimetric analyzes were evaluated. Results showed that paraquat exposure decreased cell viability, increased lipoperoxidation and apoptosis. Porphyrin treatment increased cell viability and proliferation, reactive oxygen and nitric oxide production and protein and DNA damage. O2 • −H2O2 imbalance differentially regulated the oxidative metabolism of HaCaT keratinocyte lineage via the Keap1-Nrf2 gene expression. Acai extract has also been shown to significantly decrease cell proliferation as well as the growth of formed colonies and inhibit the expression of the Bcl-2 gene, responsible for the antiproliferative effect on prostate cancer cells. We also verified that the acai berry extract showed antitumor activity in HT-29 cells by reducing cell viability and cell cycle arrest, and the acai berry antitumor activity is due to the synergistic effect of its bioactive molecules. Therefore, the results suggested that acai showed antitumor activity against prostate and colorectal cancer cells, and that oxidative stress could cause an imbalance in the epidermal cells and cause cancer. Thus, it could be used as a supplement to prevent and reduce the effects caused by oxidative stress.